Analysis the effect of investment on poverty in Indonesia year 1990-2016 (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to analysis the effect of investment on poverty in Indonesia using two analyzes : long-term equilibrium analysis with cointegration equation and short-term analysis with linear regression method ECM (Error Correction Model) period 1990-2016. Results show that domestic investment and foreign investment affect on poverty.